Profitability of Islamic Commercial Banks in the Perspective of the Covid-19 Pandemic - Munawaroh, Rifa'atul; Suseno, Bambang Dwi; Jajuli, Sulaeman (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to investigate the profitability of Islamic commercial banks from the perspective of the Covid-19 pandemic. The population in this study are all managers who lead Shari'ah Commercial Banks in Banten Province. Data collection using a questionnaire. The unique data that was successfully collected and worthy of analysis was 30 respondents. After compiling the structure of the model equations, then data analysis uses Partial Least Squares (PLS) software version 3.3.5. The results of the investigation show (1) that the coefficient value of the effect of BOPO on profitability is 0.694, which means there is a positive influence and the T-Statistics value is 7.249. (2) Evidence of the following findings shows that the coefficient of the effect of BOPO on operating income is 0.694, which means there is a positive effect. (3) The coefficient value of the effect of BOPO on NOM is 0.750, which means there is a positive effect (4) In this study we cannot prove that operating income has an effect on ROA, where the coefficient is 0.077. (5) The coefficient value of the effect of NOM on profitability is 0.227, which means there is a positive influence and the T- Statistics value is 2.076. Thus this research can provide a new perspective that the operating expenses during the Covid-19 pandemic for Islamic commercial banks have taken up quite a proportion of financing to maintain the health of employees and comply with various health protocol regulations. Meanwhile, social restrictions significantly reduce people's use of Islamic commercial bank services and this directly significantly reduces operating income. The implication is that the financing burden of Islamic commercial banks can be contingently transformed to anticipate pandemic and disaster risks as well as the transition to digital services. Future research can re-examine the relationship between operating income and the profitability of Islamic commercial banks or Islamic financing institutions.